Upaya Peningkatan Motivasi dan Kreatifitas serta Skill Menulis Teks Narasi dengan Tekhnik Parafrase Wacana Dialog Pada Siswa Sekolah Dasar - Eko Adi Sumitro; Siddik Romadhan (IAIN Palopo, 2021)
The review in this study is to expand students' movement and storytelling abilities for 5th grade students of SDN Totosan II in learning how to create an account using the exchange conversation summary method. This test model is a vehicle homeroom activity research model. The subjects of this study were fifth grade students of SD Totosan in Batang-Batang District. The sources of information used are: places and events, witnesses, and notes. Data collection techniques were carried out by observation (observation), interviews, writing tests/assignments, and document analysis. Implementation begins through the initial survey, cycle I, cycle II, up to cycle III. Some cycles consist of four stages, namely: (1) action planning; (2) implementation of actions; (3) action observation; and (4) analysis and reflection. Based on the results of the study, it was proven that the application of the paraphrasing technique of dialogue discourse was able to increase student activity during the learning process and at the same time be able to improve students' narrative writing skills.